PENGARUH PELAYANAN DAN PRODUK TERHADAP KEPUASAN PELANGGAN SERTA IMPLIKASINYA TERHADAP LOYALITAS PELANGGAN (Studi Kasus Pada Konsumen Hoka Hoka Bento Cabang Mall Pulogadung Trade Centre) - Wahyu Murti; Nurfajriah Nurfajriah (Jurnal Manajemen FE-UB, 2018)
This study aims to determine the effect of service and product on customer satisfaction and its implications on customer loyalty (case study on consumer Hoka Hoka Bento Pulogadung Trade Center mall branch).The data used in this study are primary data collected directly by the author himself through the object under study is with the customers Hoka Hoka Bento Branch Mall Pulogadung Trade Center who live on Jl. Rawa Kuning RT.003 RW.02 Pulogebang Urban Village, Cakung District, East Jakarta 13950 in September 2017 and other literature studies. Data processing method using path analysis method with SPSS tool aid 23. statistical submission in this research using Goodness of Fit Test.The result of research shows that there is significant and positive influence of service to customer satisfaction, there is significant and positive influence of product to customer satisfaction, there are significant and positive influence of service to customer loyalty, there is significant and positive influence of product to customer loyalty, there is significant and positive influence of satisfaction customers to customer loyalty, Service has an indirect effect on customer loyalty through Customer Satisfaction, the product has an indirect effect on customer loyalty through customer satisfaction. Keywords: Service, Product, Customer Satisfaction, Customer Loyalty